Intimate partner violence and HIV in ten sub-Saharan African countries: what do the Demographic and Health Surveys tell us? - Prof. Dick Durevall, PhD; Dr. Annika Lindskog, PhD (Elsevier, 2015)
Background: Many studies have identified a significant positive relation between intimate partner violence and HIV in women, but adjusted analyses have produced inconsistent results. We systematically assessed the association, and under what condition it holds, using nationally representative data from ten sub-Saharan African countries, focusing on physical, sexual, and emotional violence, and on the role of male controlling behaviour. Methods: We assessed cross-sectional data from 12 Demographic and Health Surveys from ten countries in sub-Saharan Africa. The data are nationally representative for women aged 15-49 years. We estimated odds ratios using logistic regression with and without controls for demographic and socioeconomic factors and survey-region fixed effects. Exposure was measured using physical, sexual, emotional violence, and male controlling behaviour, and combinations of these. The samples used were ever-married women, married women, and women in their first union. Depending on specification, the sample size varied between 11 231 and 45 550 women. Findings: There were consistent and strong associations between HIV infection in women and physical violence, emotional violence, and male controlling behaviour (adjusted odds ratios ranged from 1·2 to 1·7; p values ranged from <0·0001 to 0·0058). The evidence for an association between sexual violence and HIV was weaker and only significant in the sample with women in their first union. The associations were dependent on the presence of controlling behaviour and a high regional HIV prevalence rate; when women were exposed to only physical, sexual, or emotional violence, and no controlling behaviour, or when HIV prevalence rates are lower than 5%, the adjusted odds ratios were, in general, close to 1 and insignificant. Interpretation: The findings indicate that male controlling behaviour in its own right, or as an indicator of ongoing or severe violence, puts women at risk of HIV infection. HIV prevention interventions should focus on high-prevalence areas and men with controlling behaviour, in addition to violence. Funding: Swedish National Science Foundation and Gothenburg Centre of Globalization and Development, University of Gothenburg, Gothenburg, Sweden.